Pelatihan Pengolahan Pakan Ternak Fermentasi (Silase) pada Kelompok Ternak Brahma Jaya di Desa Bukit Jaya, Kecamatan Bulik Timur, Kabupaten Lamandau - Pujiastuti, Asih (Nusantara: Jurnal Pengabdian kepada Masyarakat, 2024)
The Community Service (PKM) aimed at utilizing forage (elephant grass) and solids through feed processing technology using silage, overcoming the shortage of forage for cattle, especially during the dry season, providing training regarding the use of livestock feed processing technology. In implementation, several PKM stages/methods are carried out, namely the first is a coordination meeting with the local PPL. At the coordination meeting, a discussion was held about potential problems with raising beef cattle in the Brahma Jaya Livestock Group, Bukit Jaya Village. Meanwhile, the second stage is counseling and training on processing fermented feed (silage). The results of the silage made by the farmers showed good results, namely clean, sour taste and smell, no mold, green brown in color, clear texture.